2012
DOI: 10.1073/pnas.1213295109
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the Leishmania major peroxidase–cytochrome c complex

Abstract: The causative agent of leishmaniasis is the protozoan parasite Leishmania major . Part of the host protective mechanism is the production of reactive oxygen species including hydrogen peroxide. In response, L. major produces a peroxidase, L. major peroxidase (LmP), that helps to protect the parasite from oxidative stress. LmP is a heme peroxidase that catalyzes the peroxidation of mitochondrial cytochrome c . We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…21 The LmP D211R mutant exhibited similar changes in activity (Figure 4 and Table 2). These results show that either changing electrostatic complementarity at the center of the complex or disrupting a specific ion pair is responsible for the loss of activity.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…21 The LmP D211R mutant exhibited similar changes in activity (Figure 4 and Table 2). These results show that either changing electrostatic complementarity at the center of the complex or disrupting a specific ion pair is responsible for the loss of activity.…”
Section: Resultsmentioning
confidence: 75%
“…1618 Like yeast CcP, the physiological redox partner for LmP is Cytc, and LmP also forms a stable Trp radical in CpdI. 19 In addition to the crystal structures of LmP and L. major Cytc (LmCytc), 20 the structure of the LmP–LmCytc complex is also known 21 and is very similar to that of the yeast CcP–yCytc complex (Figure 1). …”
mentioning
confidence: 93%
See 2 more Smart Citations
“…For the experimental work, we have used Leishmania major peroxidase (LmP) rather than yeast CCP. We and others have shown that LmP is structurally and functionally very similar to yeast CCP, including the structure of the LmP-cytochrome c (Cytc) complex, stability of CmpI, and formation of the active site Trp radical (15)(16)(17)(18). LmP, however, offers some advantages owing to simplified kinetics because, unlike yeast CCP, LmP has only one binding site for Cytc and k cat is independent of ionic strength (14).…”
mentioning
confidence: 99%